LUMINESCENCE IN IMAGES OF MEGASELIA SP. (RONDANI, 1856) (DIPTERA: PHORIDAE) OF THE BOLÍVAR STATE, VENEZUELA - Chang-Cova, Violeta (2022)
The fi nding of imagoes of the Megaselia sp. (Rondani, 1856) (Diptera: Phoridae) is described, which presented luminescence in their abdomen with small fl ashes of light (intermittent) in the same specimen, with yellow, green and red colors. Firefl ies are, of the arthropods, the closest to this type of manifestations, where the luciferin-substrate reacts with the enzyme luciferase to produce fl ashes of light (bioluminescence), however, it will be necessary to deepen if they were isolated cases? Is this case a biochemical reaction? If it is a new species with light properties? If they were substances from their diet that shine by themselves? or other new mechanisms or processes, not yet described. However, the emission of light in the abdomen of these three adults is an adaptation or evolution that will allow it to stand out for possible functions of attraction, reproduction, demonstration of vitality or other elements that will probably help it advance as a species.